Comparative Transcriptional Profiling and Physiological Responses of Two Contrasting Oat Genotypes under Salt Stress. Issue 1 (December 2018) - Wu, Bin; Munkhtuya, Yarvaan; Li, Jianjiang; Hu, Yani; Zhang, Qian; Zhang, Zongwen
Abstract Salinity is one of the major abiotic factors that affect productivity in oat. Here, we report a comparison of the transcriptomes of two hexaploid oat cultivars, 'Hanyou-5' and 'Huazao-2', which differ with respect to salt tolerance, in seedlings exposed to salt stress. Analysis of the assembled unigenes from the osmotically stressed and control libraries of 'Hanyou-5' and 'Huazao-2' showed that the expression of 21.92% (36, 462/166, 326) of the assembled unigenes was differentially regulated in the two cultivars after different durations of salt stress. Bioinformatics analysis showed that the main functional categories enriched in these DEGs were "metabolic process", "response to stresses", "plant hormone signal transduction", "MAPK signalling", "oxidative phosphorylation", and the plant-pathogen interaction pathway. Some regulatory genes, such as those encoding MYB, WRKY, bHLH, and zinc finger proteins, were also found to be differentially expressed under salt stress. Physiological measurements also detected significant differences in the activities of POD (76.24 ± 1.07 Vs 81.53 ± 1.47 U/g FW) in the two genotypes in response to osmotic stress. Furthermore, differential expression of 18 of these genes was successfully validated using RNA-seq and qRT-PCR analyses. A number of stress-responsive genes were identified in both cultivars, and candidate genes with potential roles in the adaptation to salinity were proposed.